The Effectiveness of A Computerized Program in Developing the Syntactical and Morphological Skills of the Secondary School Students at the Capital of Sana’a - Aljowaid, Safa'a Ali Saleh; Galib, Ahmed Hassan; Qetran, Yahya Abdullrazaq (Journal of Curriculum and Teaching Methodology, 2022)
This research aims at finding out the effectiveness of teaching a computerized program in developing the syntactical and morphological skills among the secondary grade students at the Secretariat of the Capital Sana’a schools. To accomplish this objective, the researcher has developed a list of the syntactical and morphological skills suitable for the level of first secondary grade students and a computerized program to develop such skills as well as an achievement test. Two methodological approaches have been followed in this research, namely: the quasi-experimental approach as well as the descriptive analytical approach, to measure the effectiveness of the computerized program (the treatment). The population is all schools at Al-Sabeen Educational District- the Capital of Sana’a. Khadija Bint Khuwailid School was selected as a representative sample. Many findings have been concluded, the most significant of which are: - Building a complete list of syntactical and morphological skills (written, mental and tasting), needed for the first secondary grade students, for which the present research aims to develop among the target students. - The effectiveness of the computerized program in the development of syntactical and morphological skills (written, mental and tasting), among the first secondary grade students, in general. - The effectiveness of the computerized program in developing the syntactical skills (written, mental and tasting) among the first secondary grade students. - The effectiveness of the computerized program in developing the morphological skills (written, mental and tasting) among firs secondary grade students. recomendations have been suggested based on the obtained findings The following Activating the role of technological media when teaching Arabic language, particularly with the Linguistic subjects of Syntax angy Adopting a new teaching mechanism through the use of computer, breaking up the traditional routine used in teaching.